METHODICAL GUIDELINES FOR DIAGNOSTICS, TREATMENT AND PREVENTION OF CANINE BABESIOSIS IN THE CENTRAL AREA OF THE RUSSIAN FEDERATION - M. D. Novak; O. U. Nikulina; S. V. Engashev (Российский паразитологический журнал)
Objective of research: to study distribution and features of epizootic process at canine babesiosis in the central area of theRussian Federation as well as improvement of diagnostics, treatment and prevention measures.Materials and methods: Definition of species composition and number of ticks (Ixodidae) on dogs. Statistical analysis of veterinary reports from regional veterinary stations of theRyazan region. Laboratory microscopic and serological diagnostic test for canine babesiosis.Results and discussion: Seasonal dynamics of activity of ixodid tick Dermacentor reticulates (April — June and August — October); maximal extensity of invasion with Babesia spp. (75%); average level of parasitemia in acute and super-sharp form of babesiosis in spring and autumn; clinical parameters of non-sterile immunity in adult and young animals; dependence of the degree of the severity of disease on the age of dogs were determined. The maximum parasitemia was observed in young (7-23%) and old (6-30%) animals. The average parasitemia was determined in dogs at the age of 3-7 years were 5-11%. The results of hematological and biochemical research revealed that severe acute canine babesiosis is characterized by erythropenia, decreased level of hemoglobin, haematocrit and thrombocytes, leukocytosis, increased level blood bilirubin (by 3-25 times), urea (1,5-5) and creatinine (1,2-3), reduced glucose level (up to 50%). In babesiosis of light and mild severity, the above-mentioned changes of hematological and biochemical parameters in dogs were not significant. Latent canine babesiosis might be diagnosed by serological test (RAHА) on antibodies to Babesia spp. High efficiency of domestic drugs Babesan (EE = 96,5%), Forticarb (EE = 93,3%), Piro-Stop (EE = 90,9%), Veriben (EE = 82,3%), Neosidin (EE = 75%) for babesiosis in dogs was determined. The drug Emidonol which has antioxydantic and antihypocsantic properties and was used within 5-7 days for dog treatment, promotes prevention of complications in the form of heart and respiratory failure, and reduction of recovery time. Efficiency of the drug «Bars spot-on» (containing ivermectin) applied against ixodid ticks was detected. Repellent efficiency of the essential oil-based collars «Bar», «Fitodoc» and «Chetyre s hvosticom» used against ixodidosis of dogs, was confirmed, the duration of their action is from 160 to 180 days.